SECRETORY PROTEIN EXPRESSION IN ESCHERICHIA COLI - Aksambaeva , A.S.; Shustov , A.V. (Eurasian Journal of Applied Biotechnology, 2015)
Periplasmic or extracellular secretory expression were used to produce functionally active recombinant proteins that were incorrectly folded in the cytoplasm of Escherichia coli. At least six different protein-secretion systems were described in Gram-negative bacteria (s.c. types 1-6 secretion systems, T1SS-T6SS), which differ in complexity and morphology (structures of translocons and membrane complexes). Some secretion systems perform translocation in one step (from cytoplasm directly into the extracellular milieu), while others translocate in two steps: the protein is first translocated from the cytoplasm to the periplasmic space with Sec, Tat, or SRP pathways; secondly, a different export carrier transfers the product out of the cell. This review describes the Sec (general secretory pathway), Tat (twin-arginine pathway for proteins with rapid or complex folding), and SRP (co-translational pathway) machinery for translocation from the cytoplasm to the periplasm. Despite the current understanding of the mechanisms of protein translocation and extracellular release, there is currently no effective way to theoretically predict how to produce a given recombinant protein in a secretory form other than trial and error. Given the diverse secretory apparatuses and systems in E. coli, we expect that secretory expression will be popular in research and industrial applications for cytoplasmic expression.